Tracheal tumors. Issue 4 (July 2019) - Diaz-Mendoza, Javier; Debiane, Labib; Peralta, A. Rolando; Simoff, Michael
Abstract : Purpose of review: This article provides the most recent literature and experienced guidance about diagnosis and management of tracheal tumors, including future directions. Recent findings: Tracheal tumors are challenging to diagnose given their nonspecific and late-onset symptoms. Critical airway obstruction is the most feared complication. The cornerstone in management of them is surgical resection whenever is possible. Different diagnostic tests (i.e., imaging and bronchoscopy) help in the assessment of resectability. Alternative management including interventional bronchoscopic techniques can be offered to patients who are not suitable for surgical resection. Radiation and chemotherapy can also be used as adjuvant, neoadjuvant or sole treatment in malignant tumors. Recent advances in tracheal transplantation and bioengineering with tracheal reconstruction have shown a new direction in the management of these tumors. All these topics will be discussed in this article. Summary: Despite advances in diagnostic and therapeutic techniques, tracheal tumors are still a medical challenge. Although studies are still trying to find the best surgical techniques as well as the role for chemotherapy and radiation, most recent studies are addressing tracheal reconstruction and transplantation as the new horizon for management.